2017
DOI: 10.1038/s41598-017-11360-4
|View full text |Cite
|
Sign up to set email alerts
|

Flat building blocks for flat silicene

Abstract: Silicene is the silicon equivalent of graphene, which is composed of a honeycomb carbon structure with one atom thickness and has attractive characteristics of a perfect two-dimensional π-conjugated sheet. However, unlike flat and highly stable graphene, silicene is relatively sticky and thus unstable due to its puckered or crinkled structure. Flatness is important for stability, and to obtain perfect π-conjugation, electron-donating atoms and molecules should not interact with the π electrons. The structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…The periodic calculations of BeH-terminated hexasilabenzene and planar hexasilabenzene with sufficient vacuum space between the molecules reproduce the previous gas-phase calculations. 35 That is, in both periodic and gas-phase calculations, planar BeH-terminated hexasilabenzene is the minimum, while planar hexasilabenzene is the transition state. In addition, when compared between periodic and gas-phase calculations, the Si–Si bond distances are almost equal within an error of 0.001 Å, and the lowest frequencies match within an error of 1.5 cm –1 .…”
Section: Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The periodic calculations of BeH-terminated hexasilabenzene and planar hexasilabenzene with sufficient vacuum space between the molecules reproduce the previous gas-phase calculations. 35 That is, in both periodic and gas-phase calculations, planar BeH-terminated hexasilabenzene is the minimum, while planar hexasilabenzene is the transition state. In addition, when compared between periodic and gas-phase calculations, the Si–Si bond distances are almost equal within an error of 0.001 Å, and the lowest frequencies match within an error of 1.5 cm –1 .…”
Section: Results and Discussionmentioning
confidence: 98%
“… a SP: stationary point, TS: transition state, MIN: minimum. b The result [ref ( 35 )] of gas-phase calculation is in parentheses. …”
Section: Results and Discussionmentioning
confidence: 99%
“…In specific, the B3LYP scheme, which comprises LYP and B88 is utilized in the current work owing to the accuracy exhibited by the functional in determining the electronic properties with less computational time [38]. The effective B3LYP functional is found to be utilized for the base materials silicene [39], silicene oxide [40] and silicon nanosheets [41]. B3LYP is also employed to explore the adsorption and optoelectronic properties of graphane, which is analogous to silicane (base material of the current work) [42].…”
Section: Calculation Specificationsmentioning
confidence: 99%
“…It was theoretically predicted that the Si 6 monocyclic backbone retains planar geometry when all H atoms were substituted by Li atoms . Si 6 n − ( n= 2, 4, and 6) and (SiBeH) 6 are the other theoretically known compounds possessing planar Si 6 monocyclic backbone . Exploration of the PES of Si 6 Li 6 showed that the Si 6 Li 6 monocyclic structure was not the global minimum on the PES .…”
Section: Figurementioning
confidence: 99%
“…This result would be surprising because less attention had been paid in Na‐substituted compounds than Li‐substituted ones. A recent theoretical report also shows that Na does not stabilize the planar Si 6 backbone in Si 6 Na 6 , whereas, in the backbone of 17 , 19 , and 21 , Na is the best alkali metal to stabilize the planar Si 6 backbone.…”
Section: Figurementioning
confidence: 99%